(untitled) (África, 2011)
Mia Couto is considered a special case in the field of African Lusophone writers due to the quality of his writing. His texts are imbedded of a magical, mythical world that nevertheless depicts the reality of Lusophone Africa. These characteristics together with the exceptional character of the themes on which he focuses constitute an invitation to apply to his works the concepts derived from quantum physics and the science of cognition. In this article I bring together two different structures of thought, Western and African, in an effort to give Western readers the tools to go beyond the basic approaches to Couto’s text.